The Effect of Fascia Relaxation and Mobilization of the Hyoid on the Range of Motion, Pain, and Deviation of the Hyoid in Neck Pain - Byung-jin Lee; Tae-lim Yoon (Korean Research Society of Physical Therapy, 2020)
Background: Neck pain can be caused by any structure in the neck, such as intervertebral discs, ligaments, muscles, facet joints, dura mater, and nerve roots. The hyoid bone is a structure that is also related to head and neck posture, neck movement and pain, but there are no studies on hyoid deviation, neck pain, and range of motion (ROM). Objects: The purpose of this study was to investigate the effect of fascia relaxation and mobilization of the hyoid bone on the ROM, pain, and lateral deviation of the hyoid bone. Methods: Twenty-five patients with neck pain identified by the lateral motion test (10 males [35.13 ± 7.67 years, 172.69 ± 3.90 cm, 78.77 ± 6.96 kg] and 15 females [35.13 ± 10.05 years, 161.11 ± 4.09 cm, 52.59 ± 2.98 kg]) was chosen randomly. Baseline values for pain, neck ROM, and lateral deviation in the hyoid bone were recorded using a visual analogue scale (VAS), goniometer, and tape measure. Then, each patient was treated with hyoid fascia relaxation and mobilization, and all results were recorded after intervention. Comparison of the results before and after intervention was analyzed using paird t-test (p < 0.05). Results: Right rotation, extension, VAS, and rotational asymmetry statistically significant differences (p < 0.05). Right rotation and extension increased ROM, rotational asymmetry ratio and VAS decreased. However, there was no significant difference in flexion, left rotation, center point (p > 0.05). Conclusion: Fascia relaxation and hyoid mobilization could improve the ROM of cervical extension, asymmetry of the cervical rotation and neck pain.